HUMOR SEBAGAI STRATEGI MODERASI UMAT BERAGAMA PASCATEROR BOM MAKASAR 2021 - Sahrul Romadhon; Ardi Wina Saputra (Balai Diklat Keagamaan Bandung, 2021)
In this study, response of religious moderation approach is the main study based on the uploading analysis of Catholic Social Media Accounts Garis Lucu (KGL) and NU Garis Lucu (NUGL) with total 15,050 followers. The method used in this study is qualitative with grounded theory approach, i.e. generalizing theory, action, or interaction. Based on the results, it can be concluded that the administrators of both social media accounts tend to use the dimensions of humor language strategies by a variety of humor strategies: irony, allusion, exaggeration, sarcasm, definition, and facetiounness. The humor strategy application on KGL and NUGL account became a positive culture in the social media world as well as a soothing publication that must be exemplified by other social media accounts considering that social media users are mostly millennials.Keywords: terrorism; religious moderation; humor strategy.